Auditory processing disorder (APD) in children: A marker of neurodevelopmental syndrome. (September 2013) - Moore, David R.; Hunter, Lisa L.
Abstract: Currently, there are two major hypotheses concerning the nature of developmental APD. One is conventional, that APD results from impaired 'bottom-up' processing of sounds. However, while a conventional view suggests the problem with APD lies in the central auditory nervous system (CANS), we propose that the problem may lie more peripherally, possibly in the ear. Alternatively, processing problems expressed in the ear, hindbrain or auditory cortex could reflect the second hypothesis, 'top-down' influences from cortical cognitive processing centers that may exert their influence on the auditory cortex, and be conveyed to lower targets via CANS efferent pathways. A variant of this hypothesis is that the problem may be entirely cognitive, primarily affecting language processing, attention or memory and exerting a non-specific (e.g. supramodal) effect on perception. Whichever of these hypotheses turns out to be correct, we propose that the very high co-occurrence of APD with a wide variety of other auditory- and/or language-based learning disorders may reflect a more general 'neurodevelopmental syndrome' (NDS). NDS is conceptualized as a supramodal communication disorder that captures a broad range of currently separate markers (e.g. language, literacy, attention and behavior problems) across age. Data are presented from a large pediatric audiology service to show the extensive co-occurrence between APD and other neurodevelopmental disorders.